Main Features of the Protection of Wooden Structures - Mamajonova Nodira Alisher qizi (Central Asian Journal of Theoretical and Applied Science, 2022)
The existing types of protective materials for wooden structures and elements are described. The features of materials for protection against moisture, decay, pests, and fire are described.